Solve for x
x=\frac{\sqrt{12801}-1}{6400}\approx 0.01752211
x=\frac{-\sqrt{12801}-1}{6400}\approx -0.01783461
Graph
Share
Copied to clipboard
0.08x^{2}=2.5\times 10^{-5}\left(-x+1\right)
Variable x cannot be equal to 1 since division by zero is not defined. Multiply both sides of the equation by -x+1.
0.08x^{2}=2.5\times \frac{1}{100000}\left(-x+1\right)
Calculate 10 to the power of -5 and get \frac{1}{100000}.
0.08x^{2}=\frac{1}{40000}\left(-x+1\right)
Multiply 2.5 and \frac{1}{100000} to get \frac{1}{40000}.
0.08x^{2}=-\frac{1}{40000}x+\frac{1}{40000}
Use the distributive property to multiply \frac{1}{40000} by -x+1.
0.08x^{2}+\frac{1}{40000}x=\frac{1}{40000}
Add \frac{1}{40000}x to both sides.
0.08x^{2}+\frac{1}{40000}x-\frac{1}{40000}=0
Subtract \frac{1}{40000} from both sides.
x=\frac{-\frac{1}{40000}±\sqrt{\left(\frac{1}{40000}\right)^{2}-4\times 0.08\left(-\frac{1}{40000}\right)}}{2\times 0.08}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 0.08 for a, \frac{1}{40000} for b, and -\frac{1}{40000} for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\frac{1}{40000}±\sqrt{\frac{1}{1600000000}-4\times 0.08\left(-\frac{1}{40000}\right)}}{2\times 0.08}
Square \frac{1}{40000} by squaring both the numerator and the denominator of the fraction.
x=\frac{-\frac{1}{40000}±\sqrt{\frac{1}{1600000000}-0.32\left(-\frac{1}{40000}\right)}}{2\times 0.08}
Multiply -4 times 0.08.
x=\frac{-\frac{1}{40000}±\sqrt{\frac{1}{1600000000}+\frac{1}{125000}}}{2\times 0.08}
Multiply -0.32 times -\frac{1}{40000} by multiplying numerator times numerator and denominator times denominator. Then reduce the fraction to lowest terms if possible.
x=\frac{-\frac{1}{40000}±\sqrt{\frac{12801}{1600000000}}}{2\times 0.08}
Add \frac{1}{1600000000} to \frac{1}{125000} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
x=\frac{-\frac{1}{40000}±\frac{\sqrt{12801}}{40000}}{2\times 0.08}
Take the square root of \frac{12801}{1600000000}.
x=\frac{-\frac{1}{40000}±\frac{\sqrt{12801}}{40000}}{0.16}
Multiply 2 times 0.08.
x=\frac{\sqrt{12801}-1}{0.16\times 40000}
Now solve the equation x=\frac{-\frac{1}{40000}±\frac{\sqrt{12801}}{40000}}{0.16} when ± is plus. Add -\frac{1}{40000} to \frac{\sqrt{12801}}{40000}.
x=\frac{\sqrt{12801}-1}{6400}
Divide \frac{-1+\sqrt{12801}}{40000} by 0.16 by multiplying \frac{-1+\sqrt{12801}}{40000} by the reciprocal of 0.16.
x=\frac{-\sqrt{12801}-1}{0.16\times 40000}
Now solve the equation x=\frac{-\frac{1}{40000}±\frac{\sqrt{12801}}{40000}}{0.16} when ± is minus. Subtract \frac{\sqrt{12801}}{40000} from -\frac{1}{40000}.
x=\frac{-\sqrt{12801}-1}{6400}
Divide \frac{-1-\sqrt{12801}}{40000} by 0.16 by multiplying \frac{-1-\sqrt{12801}}{40000} by the reciprocal of 0.16.
x=\frac{\sqrt{12801}-1}{6400} x=\frac{-\sqrt{12801}-1}{6400}
The equation is now solved.
0.08x^{2}=2.5\times 10^{-5}\left(-x+1\right)
Variable x cannot be equal to 1 since division by zero is not defined. Multiply both sides of the equation by -x+1.
0.08x^{2}=2.5\times \frac{1}{100000}\left(-x+1\right)
Calculate 10 to the power of -5 and get \frac{1}{100000}.
0.08x^{2}=\frac{1}{40000}\left(-x+1\right)
Multiply 2.5 and \frac{1}{100000} to get \frac{1}{40000}.
0.08x^{2}=-\frac{1}{40000}x+\frac{1}{40000}
Use the distributive property to multiply \frac{1}{40000} by -x+1.
0.08x^{2}+\frac{1}{40000}x=\frac{1}{40000}
Add \frac{1}{40000}x to both sides.
\frac{0.08x^{2}+\frac{1}{40000}x}{0.08}=\frac{\frac{1}{40000}}{0.08}
Divide both sides of the equation by 0.08, which is the same as multiplying both sides by the reciprocal of the fraction.
x^{2}+\frac{\frac{1}{40000}}{0.08}x=\frac{\frac{1}{40000}}{0.08}
Dividing by 0.08 undoes the multiplication by 0.08.
x^{2}+\frac{1}{3200}x=\frac{\frac{1}{40000}}{0.08}
Divide \frac{1}{40000} by 0.08 by multiplying \frac{1}{40000} by the reciprocal of 0.08.
x^{2}+\frac{1}{3200}x=\frac{1}{3200}
Divide \frac{1}{40000} by 0.08 by multiplying \frac{1}{40000} by the reciprocal of 0.08.
x^{2}+\frac{1}{3200}x+\left(\frac{1}{6400}\right)^{2}=\frac{1}{3200}+\left(\frac{1}{6400}\right)^{2}
Divide \frac{1}{3200}, the coefficient of the x term, by 2 to get \frac{1}{6400}. Then add the square of \frac{1}{6400} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{1}{3200}x+\frac{1}{40960000}=\frac{1}{3200}+\frac{1}{40960000}
Square \frac{1}{6400} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{1}{3200}x+\frac{1}{40960000}=\frac{12801}{40960000}
Add \frac{1}{3200} to \frac{1}{40960000} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{1}{6400}\right)^{2}=\frac{12801}{40960000}
Factor x^{2}+\frac{1}{3200}x+\frac{1}{40960000}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{1}{6400}\right)^{2}}=\sqrt{\frac{12801}{40960000}}
Take the square root of both sides of the equation.
x+\frac{1}{6400}=\frac{\sqrt{12801}}{6400} x+\frac{1}{6400}=-\frac{\sqrt{12801}}{6400}
Simplify.
x=\frac{\sqrt{12801}-1}{6400} x=\frac{-\sqrt{12801}-1}{6400}
Subtract \frac{1}{6400} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}